Your brain [videorecording (DVD)] - Bicks, Michael; Strachan, Anna Lee; Sussberg, Jason (PBS Distribution, 2023)
How does your brain create your reality? Are you in control, or is your brain controlling you? Discover the surprising answers based on the latest research in this journey into the human brain with neuroscientist Heather Berlin.